The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.08.09.503346
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering the Inter-domain Decoupling in the Gram-negative Bacterial Membrane Insertase

Abstract: YidC is a protein found in membranes that plays an important role in the process of inserting newly generated proteins into lipid membranes. The SecYEG-dependent complex is responsible for inserting proteins into the lipid bilayer, and this process is facilitated by YidC. In addition, YidC acts as a chaperone during the folding processes of proteins. Multiple investigations have conclusively shown that the gram-positive bacterium YidC has SecY-independent insertion mechanisms. Through the use of microsecond le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…There are a number of studies and reviews on how cholesterol modulates class A GPCRs, but this area of study is yet to be fully explored for class C GPCRs. Recent advances in experimental and computational power have enabled researchers to investigate the role of lipids in various membranes and solvable proteins, at the atomic level using molecular dynamics simulation [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of studies and reviews on how cholesterol modulates class A GPCRs, but this area of study is yet to be fully explored for class C GPCRs. Recent advances in experimental and computational power have enabled researchers to investigate the role of lipids in various membranes and solvable proteins, at the atomic level using molecular dynamics simulation [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopy and crystallographic studies have revealed the structure of the protein in both the inward- and outward-facing conformations [ 62 , 194 , 195 , 196 ], while Molecular dynamics (MD) simulations have been used to study the alternating access mechanisms [ 43 , 196 , 197 ]. MD is a powerful computational technique used to study the dynamics of biological macromolecules such as proteins [ 198 , 199 ], nucleic acids, and lipids [ 179 , 200 , 201 ]. It is an essential tool for studying the mechanisms of membrane transport proteins [ 106 , 184 , 202 , 203 ], including the alternating access mechanism in Pgp [ 43 , 196 , 197 ].…”
Section: Alternating Access Mechanism In Mammalian Mdrs and Bacterial...mentioning
confidence: 99%
“…There are a number of studies and reviews on how cholesterol modulates class A GPCRs, but this area of study is yet to be fully explored for class C GPCRs. Recent advances in experimental and computational power have enabled researchers to investigate the role of lipids in various membranes and solvable proteins, at the atomic level using molecular dynamics simulation [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The argument for cholesterol addition varies from the stabilization of the protein to aiding dimerization. Experimental analysis and, most recently molecular dynamics simulations [8][9][10][11][12]27] have been used to decipher the possible role of cholesterol in these protein structures. In this review, we will discuss the relevance and position of cholesterol molecules in class C GPCR structures and functions.…”
Section: Introductionmentioning
confidence: 99%